Flexible operation of grid-tied single-phase power converter - Bonaldo, Jakson Paulo; Paredes, Helmo Kelis Morales [UNESP]; Pomilio, José Antenor (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This work presents a technique to allow the use of single-phase power converter tied to the grid utility both as active power filter (APF), mitigating power quality disturbances due to the load, and as distributed generation (DG) interface, connecting a local renewable power source into the grid. The main goal is to ensure that the power processed by the power electronic converter (PEC) is lower than its rated power, contributing to increasing the lifetime and safety of the converter. The load current is decomposed, by using the Conservative Power Theory, in current components related to the non-active power consumed by the load. Then, this non-active current is weighted by a factor, which is calculated based on the load power factor, generating the reference for disturbances compensation. The reduction in the power processed by the PEC is achieved by adjusting the power factor desired in the grid side, which leads to a partial compensation of the PQ disturbances. © 2013 IEEE.
Keywords: Active Power Filter; Conservative Power Theory; Distributed Generation; Flexible Power Converter